2009
DOI: 10.1088/0963-0252/18/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Sheath structure in front of an electron emitting electrode immersed in a two-electron temperature plasma: a fluid model and numerical solutions of the Poisson equation

Abstract: A one-dimensional fluid model of sheath formation in front of a large, planar, floating, electron emitting electrode (collector) immersed in a two-electron temperature plasma is presented. For certain values of the parameters the Bohm criterion is triple valued. Three methods to select the correct Bohm velocity are compared. The simplest is to find the parameters, where the floating potentials that correspond to the high and to the low Bohm velocity are equal. But sometimes-when the electron emission is small-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
(174 reference statements)
0
12
0
Order By: Relevance
“…Such potential structures would return a fraction of the large emitted thermionic electron current for </ > < 0 with a different energy spectrum. These complex plasma potential profiles around electron-emitting probes were considered in [6], [7], and [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such potential structures would return a fraction of the large emitted thermionic electron current for </ > < 0 with a different energy spectrum. These complex plasma potential profiles around electron-emitting probes were considered in [6], [7], and [15].…”
Section: Discussionmentioning
confidence: 99%
“…This large flow of emitted thermionic electrons from a hot probe, i.e., 1 <C jthr(</>, T p )/j eo (4>, T e ) for </ > < 0, interacts with the surrounding plasma and may produce different physical effects. First, as discussed in [6], [7], and [15], the classical plasma sheath around the probe could be modified and might develop a plasma potential minimum acting as a virtual cathode. Hence, a fraction of the initially repelled electrons might return to the emissive probe with a different energy spectrum.…”
Section: Jthv(t P ) = +J R D(t P )(L -Ementioning
confidence: 99%
“…This interaction appears in experiments carried out involving plasmas [83,143] and also, in vessels flying in space [86]. Many works have provided fluid models, as the those by T. Gyergyek et al [116,144] or kinetic descriptions, as the works by M. D.Campanell et al [89,145] or J. P.Sheehan et al [98,143], as well as many other authors [23,85,[146][147][148][149][150]. Moreover, different approaches to describe the emission of electrons as the works by J. L. Domenech-Garret et al [88,113] and references therein, can be found in the literature, but the description of the complete processes involved in the plasma-wall interaction are still an open topic of discussion because of the variety and peculiarities of each plasma device.…”
Section: Plasma-wall Interactionmentioning
confidence: 96%
“…In some situations, plasmas or neutral gases may evolve from abrupt initial or boundary conditions or may generate thin structures, as layers or sheaths [18,[115][116][117], that make difficult the numerical resolution and may lead to non-physical evolutions or inaccurate solutions. For instance, collimated charges beam or localised emissive walls, as well as the electric applied field may result in an abrupt plasma evolution.…”
Section: Influence Of Self-collisions In the Evolution Of Discontinuomentioning
confidence: 99%
See 1 more Smart Citation